2000 Public Service Awards: - B. Alex White, DDS, DrPH (Blackwell Synergy, 2001)
We’re fortunate to have so many people who devote time and energy to improve the public’s oral health. We simply could not achieve all that we do to support funding of education, research, and service without the help of organizations and individuals such as those we recognize today